Performance evaluation of dextran-coated CaFe12O19/MnFe2O4 exchange-spring composites for the self-heating properties at radio frequency field - Syed, Ishtiaque; Lima, Sharmin Akter; Deb, Nandita; Al-mamun, M.; Hoque, Sheikh Manjura (Frontiers in Chemistry, 2024)
The CaFe 12 O 19 /MnFe 2 O 4 composites with the hard (CaFe 12 O 19 ) and soft (MnFe 2 O 4 ) magnetic phases, were prepared by chemical co-precipitation method. The prepared composites were calcined at three different temperatures to form different phases. The structural, morphological, and magnetic properties of composite were analyzed by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), room temperature vibrational sample magnetometer (VSM), and transmission electron microscope (TEM). The presence of the hard and soft phases has been confirmed without any secondary phase from XRD analysis, indicating the formation of composite. The crystallite size is found to be in the range of 24-44 nm calculated by Scherrer's formula. The TEM revealed hexagonal platelets of CaFe 12 O 19 with spinel MnFe 2 O 4 particles with an average particle size of 48 nm formed at the surface of the CaFe 12 O 19 /MnFe 2 O 4 nanocomposite. The room temperature magnetic properties of composite were evaluated by employing VSM. The magnetic measurements have displayed enhancement in coercivity and magnetization for CaFe 12 O 19 /MnFe 2 O 4 , indicating that the composite possessed excellent exchange coupling. The composite's enhanced energy product((BH) max ) made it highly promising for biomedical applications such as hyperthermia. The exchange-spring coupled magnetic composite was coated with dextran to make it biocompatible, which is necessary for hyperthermia applications. The coating was confirmed using Fourier transform infrared spectroscopy (FTIR). Cytotoxicity tests on Vero cell lines showed that the coated composites had an excellent (>95%) cell survival rate. The hyperthermia heating of composite was measured for different concentrations of composite (0.25, 0.5, 1, 2, and 4 mg/ml) from which specific loss power (SLP) was calculated. From these SLP values, the optimized concentration was identified.